Calorimetric study of the interactions between surfactants and dextran modified with deoxycholic acid - Guangyue Y Bai (2010)
Dextran modified with deoxycholic acid (Dex-DCA) was synthesized by grafting DCA along the polymer backbone, with degrees of substitution (DS)-2% and 3%. The thermodynamics of the association processes of the mixed systems is followed by isothermal titration calorimetry for sodium deoxycholate/sodium dodecyl sulfate (NaDCA/NaDS), Dex-DCA with different surfactants-Dex-DCA/NaDS, Dex-DCA/NaDCA, and Dex-DCA/DTAB (dodecyltrimethylammonium bromide). Calorimetric measurements for the micellization processes of the pure surfactants in aqueous solution were also performed for comparison with the results obtained for the mixed systems. We have obtained and herein present the enthalpies of micelle formation and critical micelle concentrations for the referred pure surfactants, as well as the interaction and aggregation enthalpies for the mixed systems-surfactant/polymer. The dependence of the observed aggregation behavior on the surfactant and temperature is discussed in detail. Finally, we should stress that calorimetry allowed us to ascertain a very important fact in polymer/surfactant interaction. From the comparison between NaDCA/NaDS and Dex-DCA/NaDS calorimetric titration curves, we could clearly see that the interaction between Dex-DCA and NaDS is driven by the interaction between the bile acid moiety and the surfactant.